Digital Financial Inclusions for Sustainable Growth: Employing Natural Resources through Digital Governance - Ghaffar, Abdul; Asif, Muhammad; Ejaz, Areeba; Raza, Kashif (Journal of Environmental and Energy Economics, 2025)
Digital financial inclusion (DFI) initiatives have transformed the economy and environment by providing previously underbanked regions with enhanced access to banking, payment processing, and other financial services. This study analyses the correlations among DFI, GDP growth, and ecological sustainability, using the rapid expansion of digital finance in China as a case study. The research used econometric models to examine the impact of DFI on GDP growth and CO₂ emissions, including factors such as renewable energy adoption, industrial efficiency, and trade patterns. This purpose employs panel data from many national and international sources. The results demonstrate that reduced carbon intensity and improved economic inclusion correlate with heightened DFI penetration. Improved resource allocation, less travel for transactions, and increased green investment flows contribute to lower carbon intensity. The results suggest that DFI may fulfil climate action goals while promoting equitable growth, benefiting policymakers aiming to include financial innovation in sustainable development plans.